1985
DOI: 10.1126/science.3931222
|View full text |Cite
|
Sign up to set email alerts
|

A Common Origin pf Rickettsiae and Certain Plant Pathogens

Abstract: On the basis of ribosomal RNA sequence comparisons, the rickettsia Rochalimaea quintana has been found to be a member of subgroup 2 of the alpha subdivision of the so-called purple bacteria, which is one of about ten major eubacterial divisions. Within subgroup alpha-2, R. quintana is specifically related to the agrobacteria and rhizobacteria, organisms that also have close associations with eukaryotic cells. This genealogical grouping of the rickettsiae with certain plant pathogens and intracellular symbionts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 19 publications
2
54
0
2
Order By: Relevance
“…To clarify the phylogenetic relationships of the species belonging to the genera Sphingomonas and Rhizomonas and Erythrobacter longus, we determined the 16s rRNA sequence of Rhizomonas suberifaciens I F 0 1521 lT (Fig. 1) and compared it with the sequences of eight species belonging to the genus Sphingomonas (29), the sequences of the bacteriochlorophyll-containing bacteria Porphyrobacter neustonensis (4) and Roseobacter denitriJicans (22), and the sequences of 30 other species belonging to the alpha subclass (30,40), Magnetospirillum magnetotacticum (2), and Rhodospirillum rubrum (30,40); alpha-2 group species Hyphomicrobium vulgare (25), Rhodomicrobium vanniefii (40), Ancyfobacter aquaticus (39), Afipia felis (37), Blastobacter denitrificans (37), Bradyrhizobium japonicum (37), Methylosinus trichosporium (30), Methylobacterium organophilum (30), Agrobacterium tumefaciens (30,40), Bartonella bacilliformis (18), Rochalimaea quintana (36), Caulobacter bacteroides (27), and Pseudomonas diminuta (30); alpha-3 group species Hyphomonas jannaschiana (25), Hirschia baltica (21), Paracoccus denitr$cans (15,40), Rhodobacter capsufatus (30,40), and Roseobacter denitrificans (4); alpha4 group species Erythrobacter longus (40) and Porphyrobacter neustonensis (4); alpha group species Cowdria ruminantium (3), Ehrlichia risticii (34,35), Rickettsia prowazekii (35), and Wolbachia pipientis (16); delta-3 group species Escherichia coli (30). Bar = 0.01 K,,, unit.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify the phylogenetic relationships of the species belonging to the genera Sphingomonas and Rhizomonas and Erythrobacter longus, we determined the 16s rRNA sequence of Rhizomonas suberifaciens I F 0 1521 lT (Fig. 1) and compared it with the sequences of eight species belonging to the genus Sphingomonas (29), the sequences of the bacteriochlorophyll-containing bacteria Porphyrobacter neustonensis (4) and Roseobacter denitriJicans (22), and the sequences of 30 other species belonging to the alpha subclass (30,40), Magnetospirillum magnetotacticum (2), and Rhodospirillum rubrum (30,40); alpha-2 group species Hyphomicrobium vulgare (25), Rhodomicrobium vanniefii (40), Ancyfobacter aquaticus (39), Afipia felis (37), Blastobacter denitrificans (37), Bradyrhizobium japonicum (37), Methylosinus trichosporium (30), Methylobacterium organophilum (30), Agrobacterium tumefaciens (30,40), Bartonella bacilliformis (18), Rochalimaea quintana (36), Caulobacter bacteroides (27), and Pseudomonas diminuta (30); alpha-3 group species Hyphomonas jannaschiana (25), Hirschia baltica (21), Paracoccus denitr$cans (15,40), Rhodobacter capsufatus (30,40), and Roseobacter denitrificans (4); alpha4 group species Erythrobacter longus (40) and Porphyrobacter neustonensis (4); alpha group species Cowdria ruminantium (3), Ehrlichia risticii (34,35), Rickettsia prowazekii (35), and Wolbachia pipientis (16); delta-3 group species Escherichia coli (30). Bar = 0.01 K,,, unit.…”
Section: Resultsmentioning
confidence: 99%
“…A similarity matrix was constructed with other eubacterial sequences by using a data base that included approximately 400 partial (oligonucleotide) 16s rRNA sequences from bacteria (11, 48; C. R. Woese, personal communication). Sequences from the following bacteria were selected, each representative of a major phylogenetic group: Agrobacterium tumefaciens (alpha subdivision of purple bacteria) (42,47), Pseudomonas testosteroni (beta subdivision of purple bacteria) (31, 49), Chromatium vinosum and Legionella pneumophila (gamma subdivision of purple bacteria) (48; C. R. Woese, personal communication), Desulfovibrio desulfuricans (delta subdivision of purple bacteria) (48; C. R. Woese, personal communication), and Bacillus subtilis (gram positive) (12). Sequences were decomposed into RNase T1 oligonucleotides, stretches of bases that contain no guanosine but end in a single G. These were compared by signature analysis with existing T1 oligonucleotide catalogs available for various bacteria including Xanthomonas maltophilia and X .…”
Section: Methodsmentioning
confidence: 99%
“…Methylobacterium nodulans ' is the name suggested for a recently discovered fourth group of root-nodule bacteria that are methylotrophic and closely related to known Methylobacterium species (Sy et al, 2001). The other rhizobia, known collectively as the fast-growers, are more closely related, but their clade in the SSU phylogeny (Maidak et al, 2000) also includes Agrobacterium ( plant gall-formers), Phyllobacterium (leaf and rhizosphere colonists), Mycoplana (branching soil bacteria), Brevundimonas bullata (formerly Mycoplana bullata, see Abraham et al, 1999) and possibly the animal pathogens Bartonella and Brucella (Moreno et al., 1990 ;Weisburg et al, 1985 ;Young et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Methylobacterium nodulans ' is the name suggested for a recently discovered fourth group of root-nodule bacteria that are methylotrophic and closely related to known Methylobacterium species (Sy et al, 2001). The other rhizobia, known collectively as the fast-growers, are more closely related, but their clade in the SSU phylogeny (Maidak et al, 2000) also includes Agrobacterium ( plant gall-formers), Phyllobacterium (leaf and rhizosphere colonists), Mycoplana (branching soil bacteria), Brevundimonas bullata (formerly Mycoplana bullata, see Abraham et al, 1999) and possibly the animal pathogens Bartonella and Brucella (Moreno et al., 1990 ;Weisburg et al, 1985 ;Young et al, 1991).There has been controversy over the relationship between Agrobacterium and Rhizobium, which have long been recognized as close relatives (Fred et al, 1932). Some authors suggested that Agrobacterium should be subsumed into Rhizobium (de Ley, 1968 ; Graham, 1964 Graham, , 1976 Heberlein et al, 1967 ; Kerr, 1992 ;Sawada et al, 1993 ;White, 1972), but the splitting of Sinorhizobium and Mesorhizobium from Rhizobium weakened the case for such an amalgamation because it was not clear whether Agrobacterium formed a monophyletic clade with Rhizobium sensu stricto.…”
mentioning
confidence: 99%